Development Concept of the Dubrovnik Passenger Port for Accommodation of Large Cruise Vessels - Perko, Nina; Đurković, Vlaho; Jolić, Natalija (Promet - Traffic&Transportation, 2007)
The technical, traffic and economic parameters of the p011of Dubrovnik, specialized in goods traffic, allow for its reorganizationand conversion into a multi-purpose terminal able toaccommodate cruise ships. The following is required for its successfulconversion: development strategy analysis, financial ratioanalysis and conversion effect analysis. The paper providesthe definition and analysis of the components affecting theidentification of the port of Dubrovnik space requirements withthe aim of defining possible indicators of the port future dimensionswith respect to both, its sea and land area. The pwpose ofthis study is to reveal the advantages and disadvantages of theport of Dubrovnik as a passenger port with respect to both thenational liners and international cn1isers. The questions relatedto finding the optimal solutions for the port facilities and servicescan only be resolved by perceiving all the factors impactingthe traffic in the port, no matter whether marine or overlandconnecting the port with the highway and the airport.